Pleomorphic Invasive Lobular Carcinoma of the Breast With Extracellular Mucin and HER2 Amplification. (November 2020) - Burky, Matthew J; Ray, Emily M; Ollila, David W; O'Connor, Siobhan M.; Hertel, Johann D.; Calhoun, Benjamin C
Invasive lobular carcinoma with extracellular mucin is an uncommon pattern of invasive breast carcinoma. The 5th Edition of the World Health Organization Classification of Breast Tumors states that it is unknown whether these tumors are a subtype of mucinous carcinoma or invasive lobular carcinoma. Invasive lobular carcinoma with extracellular mucin frequently presents as a palpable mass and may be more likely to be grade 2 to 3 and HER2-positive than classic invasive lobular carcinoma. This case of pleomorphic invasive lobular carcinoma with extracellular mucin was detected by imaging only and was HER2-amplified, suggesting that a subset of these tumors may be clinically occult with an aggressive phenotype. Invasive lobular carcinoma with extracellular mucin is infrequently encountered and awareness of this entity is helpful in avoiding misdiagnosis.